Bystander Intervention Among College Men: The Role of Alcohol and Correlates of Sexual Aggression. (October 2016) - Orchowski, Lindsay M.; Berkowitz, Alan; Boggis, Jesse; Oesterle, Daniel
Current efforts to reduce sexual violence in college campuses underscore the role of engaging men in prosocial bystander behavior. The current study implemented an online survey to explore associations between engaging in heavy drinking and attitudes toward bystander intervention among a sample of college men ( N = 242). Correlates of sexual aggression were also explored as mediators of the hypothesized relationship between engaging in heavy drinking and attitudes toward bystander intervention. Data indicated that men who engaged in two or more episodes of heavy drinking over the past month reported lower prosocial bystander attitudes compared with men who did not engage in such behavior. The association between engaging in heavy drinking and lower prosocial bystander attitudes was mediated by men's perception of their peers' approval for sexual aggression, their own comfort with sexism, and engagement in coercive sexual behavior. Implications for sexual assault prevention are discussed.